Odpowiedzi

2009-12-03T16:45:08+01:00
A) (x-5)(x+5)=(x-3)²
x²-25= x²-6x+9
x²-x²+6x=9+25
6x=34 |:6
x=5⅔

b) (2a-1)²=(2a+1)(2a-1)
4a²-4a+1=4a²-1
4a²-4a -4a² = -1-1
-4a= -2 |:(-4)
a= ½

c)(3x+2)(3x-2)-9(x+1)²=-22
9x²-4-9 (x²+2x+1)= -22
9x²-4-9x² - 18x-9= -22
-18x= -22+4+9
-18x= -9 |(-18)
x= ½

d)4x(2-x)+12=-(2x+6)(2x-6)
8x-4x²+12=-(4x²-36)
8x-4x²+12= -4x²+36
8x-4x²+4x²= 36-12
8x=24 |:8
x= 3

proszę;]
1 5 1
2009-12-03T16:58:44+01:00
A) (x-5)(x+5)=(x-3)²=x²-25=x²-6x+9
x²-x²+6x=9+25
6x=34/:6
x=5,6

b) (2a-1)²=(2a+1)(2a-1)=
4a²-4a+1=4a²-1
4a²-4a²-4a=-1+1
-4a=0/:(-4)
a=0

c)(3x+2)(3x-2)-9(x+1)²=-22
9x²-4-9(x²+2x+1)=-22
9x²-4-9x²-18x-9=-22
9x²-9x²-18x=-22+4+9
-18x=-9/:(-18)
x=9/18
x=1/2

d)4x(2-x)+12=-(2x+6)(2x-6)
8x-4x²+12=-4x²+36
8x-4x²+4x²=36-12
8x=24/:8
x=3